BEHAVIOUR OF NUTRITIVE ELEMENTS AND HEAVY METALS IN CAI RIVER MOUTH AND NHA TRANG BAY - Vinh, Le Thi; Thom, Pham Thi; Thu, Nguyen Hong; Kiem, Duong Trong; Tam, Pham Huu (Vietnam Journal of Marine Science and Technology, 2007)
The behaviour of nutrients (N and P) and heavy metals (Zn, Cu, Pb and Fe) was investigated of Cai river mouth and southwest side of Nha Trang bay. The acquired results showed that: P, Pb and Fe total concentrations decreased noticeably in sea water area while N decreased insignificantly. They were mainly accumulated in river (lower Xuan Phong dam) and nearby Cai river mouth. This area could be expanded in flooding period. Contrarily, Zn and Cu rarely participated in the formation of floes (they mainly existed in dissolved phase). Deposited materials were derived from natural sources and substances formed when flocculation occurs in the freshwater-saltwater transition area. They were mainly N, P, Pb and Fe. Material exchange between dissolved and suspended phase was found only in the case of Pb. Nutritive elements and heavy metal contents in mud fraction of sediment were higher in river and river mouth area. Deposition rate of N and P was rather high in Nha Trang bay. Among the heavy metals, Fe and Pb were higher accumulation rate in comparison with Cu and Zn. The building of Xuan Phong dam of salt prevention can increase the accumulation of these contaminants in river bed sediment.